Antarctic sea-ice and palaeoproductivity variation over the last 156,000 years in the Indian sector of Southern Ocean - Ghadi, Pooja; Nair, Abhilash; Crosta, Xavier; Mohan, Rahul; Manoj, M.C.; Meloth, Thamban (Marine Micropaleontology, 2020)
International audience